2021
DOI: 10.1186/s12953-021-00175-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and ultrastructural analysis of Hermetia illucens (Diptera: Stratiomyidae) larval peritrophic matrix

Abstract: Background The black soldier fly (Hermetia illucens) has significant economic potential. The larvae can be used in financially viable waste management systems, as they are voracious feeders able to efficiently convert low-quality waste into valuable biomass. However, most studies on H. illucens in recent decades have focused on optimizing their breeding and bioconversion conditions, while information on their biology is limited. Methods About 200 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 101 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The morphological and transcriptomic analysis of the BSF larvae midgut has shown the unique digestive and transformative capabilities that helps them to adapt to different food substrates . Aligned with the findings from the present study, proteome analysis of BSF larval developmental stages revealed three physiological processes, including the insulin pathway for feed metabolism, fatty acid synthesis, and immune regulatory pathways. , …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The morphological and transcriptomic analysis of the BSF larvae midgut has shown the unique digestive and transformative capabilities that helps them to adapt to different food substrates . Aligned with the findings from the present study, proteome analysis of BSF larval developmental stages revealed three physiological processes, including the insulin pathway for feed metabolism, fatty acid synthesis, and immune regulatory pathways. , …”
Section: Discussionsupporting
confidence: 85%
“…25 Aligned with the findings from the present study, proteome analysis of BSF larval developmental stages revealed three physiological processes, including the insulin pathway for feed metabolism, fatty acid synthesis, and immune regulatory pathways. 9,10 The gut metaproteomic analysis that was performed in this study also enabled some insight to the diversity of bacterial genera. Actinobacteria, and more specifically the Actinomycetia order, returned the largest number of peptides, and Proteobacteria was the second major contributor, with most peptides derived from the Gammaproteobacteria class.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteome of the BSFL peripheral matrix revealed that BSFL gut protein digestion mainly relies on proteases. BSFL gut protein digestion enzymes mainly include trypsin and peptidase ( Lin et al, 2021 ). Pepsin is rarely found in insect guts.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae were harvested during the prepupae period at the age of 25 days. Larvae were reared at a temperature of 33°C–40°C, with a relative humidity of 60%–70% ( Lin et al , 2021 ). BSF prepupae were washed ( Fig.…”
Section: Methodsmentioning
confidence: 99%